Epithelial cell types and their evolution in the rat mammary gland determined by immunological markers. - Dulbecco, R (1983)
We have used immunological reagents for characterizing epithelial cell types in the adult rat mammary gland. Some were sera against purified proteins; others were monoclonal antibodies to mammary cells. On the basis of marker distribution we have identified 10 different cell types. We have established the developmental connection between these types by adopting the principle that cells displaying the same markers are directly related to each other. The results concur with those previously obtained by studying the growth response of mammary cells to the hormonal changes of the estrus cycle.